The Mediating Role of Patient Satisfaction in the Relationship Between Service Quality, Brand Image, and Patient Loyalty - Ni Luh Sri Dewi Indrayani; Ni Luh Putu Indiani; I Made Suniastha Amerta (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of service quality and brand image on inpatient loyalty at the Praja Amerta Pavilion of Wangaya Regional General Hospital, Denpasar, with patient satisfaction as a mediating variable. This research employs a quantitative approach using an explanatory research design. The population consists of inpatients at the Praja Amerta Pavilion, and data were collected from 160 respondents through questionnaires using a Likert scale. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement model and structural model. The results indicate that service quality has a positive but not significant effect on patient loyalty, suggesting that improvements in service quality alone are not sufficient to directly enhance patient loyalty. Conversely, brand image has a positive and significant effect on patient loyalty, indicating that a strong hospital image increases patients' trust and intention to reuse the service. Furthermore, both service quality and brand image have a positive and significant effect on patient satisfaction. Patient satisfaction also has a positive and significant influence on patient loyalty. Mediation analysis reveals that patient satisfaction fully mediates the relationship between service quality and patient loyalty and partially mediates the relationship between brand image and patient loyalty. These findings highlight that patient loyalty in healthcare services is shaped by the interaction between service quality, brand image, and patient satisfaction. Therefore, hospitals should improve service quality, strengthen brand image, and continuously manage patient satisfaction to enhance patient loyalty